Designing Institutional Framework for Political Parties in Indonesia: Democratic Analysis and Party Autonomy - M. Reza Saputra; Taufiqurrohman Syahuri; Ahmad Ahsin Thohari (Journal of State Democracy, 2026)
This study examines the institutional design of political parties in Indonesia post-Reformation, which is hindered by state intervention through mandatory legal entity status under Law Number 2 of 2011. Utilizing normative legal research and comparative legal analysis with Germany, Sweden, and the UK, this study analyzes how the administrative authority of the Ministry of Law and Human Rights is frequently misused to intervene in internal party disputes, thereby undermining party autonomy. Findings indicate that the current legal entity regime functions as an instrument of executive political control rather than neutral administration, contradicting the principle of legal certainty. This research recommends a five-pillar institutional model, including: separating legal entity status from electoral participation requirements, establishing the General Elections Commission (KPU) as the sole neutral entry point for registration, transferring dispute resolution to independent courts, internal democratization via term limits, and strengthening financial transparency. These reforms aim to restore party independence as an accountable democratic pillar, free from oligarchy and state manipulation.